(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
تم تقييم ستة آباء وهجنها نصف التبادلية لبعض مؤشرات التبكير. هدفت الدراسة إلى تحديد أفضل المتآلفات الأبوية من خلال تقدير تأثيرات مقدرتي التآلف العامة والخاصة للطرز الوراثية المدروسة ، تقدير قوة الهجين قياساً لمتوسط وأفضل الأبوين للصفات المدروسة في الهجن نصف التبادلية الناتجة ، تحديد طبيعة الفعل المورثي الذي يتحكم بصورةٍ رئيسة في إظهار المعالم الوراثية لقياسات التبكير. أظهرت نتائج الدراسة سيادة تباينات مقدرة التآلف العامة لمعظم المؤشرات المدروسة، وهذا يشير إلى أن الفعل الوراثي الإضافي هو السائد ، في حين تميزت صفة عدد الأيام حتى الإنبات بسيطرة تباينات مقدرة الائتلاف الخاصّة الأمر الذي يعكس سيطرة التأثير الوراثي غير الإضافي لهذه الصفة. وقد تفوقت الهجن التالية: Dasargelo ×Douce Provence لمؤشر عدد الأيام حتى الإنبات ، Douce Provence ×Mutant-3 لمؤشر عدد الأيام حتى الإزهار ، Dasargelo ×Mutant-3 لصفة عدد السلاميات حتى الزهرة الأولى ، Nassra ×Dasargelo لصفة طول السلامية. The study aimed to determine the best parental combinations through estimating the effects of general and specific combining ability of the studied genotypes, estimation of mid and better- parent heterosis for studied characters in half – diallel crosses, and determination of the nature of gene action which mainly controls the showing of genetic parameters of the studied traits. The results showed the dominance of variances of general combining ability for most studied parameters. This refers to the dominance of the additive gene effect, but the trait of the number of germination days was characterized by controlling the variances of the specific combining ability. This reflects the dominance of non additive gene effect. The best hybrids were: Douce Provence x Dasargelo for the number of days until the germination, Mutant-3 x Douce Provence for the number of days till the flowering, Mutant-3 x Dasargelo for the number of internodes to the first flower and Dasargelo x Nassra for the internode’s length.